Leaf traits and herbivore selection in the field and in cafeteria experiments - Pérez Harguindeguy, Natalia (2003)
Despite the vast diversity and complexity of herbivores, plants and their interactions, most authors agree that a small number of components of leaf quality affect preference by generalist herbivores in a predictable way. However, herbivore preference is determined not only by intrinsic plant attributes and herbivore biology but also by the environmental context. Within this framework, we aimed to analyse general interspecific trends in the association between herbivory and leaf traits over a wide range of angiosperms from central Argentina. We (i) tested for consistent associations between leaf traits, consumption in the field, and preference of generalist invertebrate herbivores in cafeteria experiments; (ii) assessed how well herbivore preferences in cafeterias matched leaf consumption in the field; and (iii) developed a simple conceptual model linking leaf traits, herbivore preference in cafeterias and consumption in the field. In general, we found that tender leaves with higher nutritional quality were preferred by herbivores, both in the field and in cafeteria experiments. According to our model, this relationship between field and cafeteria consumption and leaf quality is observed when generalist herbivores and plants of high accessibility are considered. However, differences between leaf consumption in the field and in cafeteria experiments can also be found. At least two reasons can account for this: (i) specialized plant–herbivore relationships often occur in the field, whereas cafeteria experiments tend to consider only one or a few generalist herbivores; (ii) different plant species growing in the field often differ in their degree of accessibility to herbivores, whereas in cafeteria experiments all species are equally accessible. Our results add new evidence to a growing consensus that, although herbivory in the field is determined by many factors, consistent patterns of differential susceptibility to foliar feeders can be found in leaves differing in nutritional quality and thus in resource‐use strategy.